ENDOVASCULAR CHEMOEMBOLIZATION OF THE HEPATIC ARTERY - A MODERN METHOD OF LOCAL CHEMOTHERAPY OF MALIGNANT LIVER LESIONS - V. E. Zagaynov; E. G. Sharabrin; E. M. Zagaynov; A. A. Zaytsev; A. A. Seregin (Креативная хирургия и онкология)
The paper deals with the review of literature devoted to one of the most important issues of contemporary oncology: treatment of malignant liver tumors. Much attention is paid to the analysis of modern endovascular treatment methods research, namely – transcatheter chemoembolization of the hepatic artery. The morphological and functional bases of chemoembolization are described in detail. The comparison between chemoembolization drugs are noted in the article, too. The results of research are shown. The conclusions about the efficiency that allows achieving positive dynamics and stabilization of the process are drawn.